The Effect of Changes in the Indonesian Mortality Table on Pension Fund Calculations Using the Projected Unit Credit Method - Hidayat, Agus Sofian Eka; Lubus, Audrey Delfina; Gunawan, Mayla Uma; Zahra, Nasywa Faridah Annisa; Mely Sintia, Ni Gusti Kadek Ari (Journal of Actuarial, Finance, and Risk Management, 2024)
Companies are required to prepare a pension fund for their employees as a form of appreciation and compensation for the services that have been given to the companies. In Indonesia, the calculation of pension funds is regulated in the Financial Services Authority Regulation (POJK) number 3 concerning Pension Fund Investments. Projected Unit Credit uses the distribution of pension benefits that pension participants will get if they work until they reach normal retirement age with a total of years of service. In this research, the researchers are using two mortality tables on the value of pension funds using the projected unit credit method. The data in this research uses salary data from PT. XYZ with the assumption of retirement age at the age of 58, and an interest rate of 6.25% based on Bank Indonesia’s rate. The results of this research show that changes in normal cost and actuarial liability for both males and females are visible at the age of entry into employment until the middle of the working period, while the effect of changes in the mortality table at the final age approaching retirement is not very significant.